2018
DOI: 10.1139/cjc-2018-0165
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of inorganic salts as a heat sink for the magnesiothermic reduction of silica

Abstract: In this study, the effectivity of a series of inorganic salts, sodium chloride, calcium chloride, magnesium chloride, potassium chloride, and sodium bromide as heat sinks during magnesiothermic reduction of silica to porous silicon was investigated. The salts were chosen based on cost, thermal stability, ability to remain chemically inert during the reduction process, and ease of removal after the reaction. The structural integrity of the spherical porous silicon nanoparticles was observed using scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…27 Various inorganic salts, such as NaCl, KCl, CaCl, and MgCl 2 , are generally used as heat absorbents that collect the excess heat from exothermic reactions. [28][29][30] Therefore, the choice of heat absorbent is crucial for controlling the exothermic reaction of the magnesiothermic reduction, as they are critical in determining the morphology and microstructure of SiO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Various inorganic salts, such as NaCl, KCl, CaCl, and MgCl 2 , are generally used as heat absorbents that collect the excess heat from exothermic reactions. [28][29][30] Therefore, the choice of heat absorbent is crucial for controlling the exothermic reaction of the magnesiothermic reduction, as they are critical in determining the morphology and microstructure of SiO x .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, microstructural changes in SiO x , such as the formation of secondary phases (eg, Mg 2 Si and Mg 2 SiO 4 ) and abnormal growth of Si crystals, are induced 27 . Various inorganic salts, such as NaCl, KCl, CaCl, and MgCl 2 , are generally used as heat absorbents that collect the excess heat from exothermic reactions 28‐30 . Therefore, the choice of heat absorbent is crucial for controlling the exothermic reaction of the magnesiothermic reduction, as they are critical in determining the morphology and microstructure of SiO x .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been demonstrated that due to the exothermic nature of the reaction, carrying out the entirety of the reaction at 650 °C results in significant morphological damage and lowering of surface area of mp-Si formed . A demonstrated method to circumvent this issue involves the addition of various inorganic salts to the reaction as a heat sink to minimize the sintering of Si nanoparticles, , but this has not been shown to produce porosity at the same level that can be achieved by using methods that involve reduction of SiCl 4 precursor in the presence of inorganic salt templates . Furthermore, addition of an extra reagent to the process can increase the overall cost of the reaction as well as the amount of solvent required to remove the heat sink, rendering such methodologies undesirable for large-scale production.…”
Section: Introductionmentioning
confidence: 99%